Barriers to Pap Smear Test for the Second Time in Women Referring to Health Care Centers in the South of Tehran: A Qualitative Approach - Laleh Hassani; Tahereh Dehdari; Ebrahim Hajizadeh; Davoud Shojaeizadeh; Mehrandokht Abedini; Saharnaz Nedjat (Shiraz University of Medical Sciences, 2017)
Background: Cervical cancer is a preventable disease with a regular screening program. Many studies have reported a large number of barriers that women had for the first time, but this study decided to find other barriers for the second time pap smear. Methods: In this qualitative research, data were gathered through in-depth interviews and expressed through conventional content analysis in the form of constant comparison. The participants were 15 women with family profile at 30 health care centers who lived in the south of Tehran and had done Pap smear for one time but didn't do it for the second time. Results: Three main themes emerged from the analysis of the interviews: negative experiences of the first Pap test were as follows: results of the first time test, readiness for performing the test, getting the test itself, and the site of the first Pap test. Personal barriers to getting the second Pap test were: inattention to time, physical barriers to the second Pap test, and inhibitory beliefs. Perceived social barriers to getting the second Pap test with two sub-themes included social supports and abstract norms. Conclusion: This study provided other barriers about Pap smear including lack of the spouse's support, the role of health care providers and physicians in screening program for early diagnosis in women.